Soil phosphorus fractions and distributions in estuarine wetlands with different climax vegetation covers in the Yellow River Delta - Fanzhu Qu; Ling Meng; Jiangbao Xia; Haosheng Huang; Chao Zhan; Yunzhao Li (Ecological Indicators, 2021)
To evaluate the relationship between phosphorus (P) fractions and physicochemical characteristics in soils of estuarine wetlands with different climax vegetation covers, surface 60-cm soil samples were collected in Suaeda heteroptera wetlands (SH), Tamarix chinensis wetlands (TC) and Phragmites australis wetlands (PA) in the Yellow River Delta during June 2017. Results showed that the inorganic phosphorus (Pi) in PA soils was significantly lower than that in TC and SH soils (p < 0.05), and the organic phosphorus (Po) showed the opposite pattern, with a rank of PA ≫ TC > SH. The available phosphorus (AP) had a high proportion at surface layer and decreased with increasing depth, with a rank of SH > TC > PA. D.HCl-Pi was the main component of the extracted Pi in all soil profiles, while C.HCl-Po, NaOH-Po and Bicarb-Po were the main components of the extracted Po in PA, TC and SH soils, respectively. Most of the Pi fractions were significantly positively correlated with Ca, Al and Fe in TC soils, whose correlations were better than those of SH and PA soils, and the Pi fractions were negatively correlated with the pH and sand contents. Our findings confirmed the complexity of the combination and unavailability of P fractions extracted by strong acids. Decreasing of sum of Po fractions (from14.72% in PA to 11.28% in SH) across a soil salinity gradient (1.0‰ to 12.0‰) provided valuable evidence of the mineralization of soil Po and that P. australis can enhance the biological functions of P. Although difference test revealed clear differences in soil physicochemical properties and slightly clear differences in P fractions, we did not extrapolate real correlations between soil P fractions and climax vegetation covers in this study. Research on the biological mechanism of climax vegetation covers and its influences on the plant absorption and utilization of P is our future direction.